Formulation and optimization of Syzygium polyanthum leaf patch as a potential diabetic wound healing using Box-Behnken design - Tahara Dilla Santi; Aryandi Darwis; Nasyata Safira (Poltekkes Kemenkes Bandung, 2026)
ABSTRACT Background: Pathological changes in the body due to diabetes mellitus interfere with the wound healing process. Syzygium polyanthum leaves contain abundant phenolic compounds and act as anti-inflammatory, antioxidant and antibacterial enabling them to play a crucial role in the healing of diabetic wounds. Patches are an effective drug delivery method because they are easy to control the release, easy to obtain and affordable for the general public. Objective: The purpose of study was to identify the best formulation and optimization of bay leaf patches as a potential for healing diabetic wounds. Methods: Syzygium polyanthum leaves were extracted using maceration techniques and compound identification using Gas Chromatography-Mass Spectrometry (GC-MS). The procedure for figuring out the ideal patch involved utilizing the Box-Behnken Design technique, which looked at three different things: bay leaf extract (BLE), polyvinyl pyrrolidone (PVP), and ethyl cellulose. The observed responses included air content (%), weight, and thickness. Results: The results of the GC-MS test obtained Tetradecanoic acid, 12-methyl - methyl ester, Estra-1,3,5 (10)-trien-17 ß-ol, n-Hexadecanoic acid, 9,10-Secocholesta-5,7,10(19) -triene-3,24, 25 triol, (3ß, 5Z,7E), Stigmasta-3,5-diene, Ergosta-5,22-dien-3-ol, acetate, (3ß,22E) . ANOVA analysis showed that the quadratic model was appropriate because it produced high R² values ​​and low PRESS values ​​for weight and thickness responses (p-value <0.0500). Conclusion: The optimal formulation for bay leaf patch was 117.271 mg of BLE, 396.274 mg of ethyl cellulose, and 227.237 mg of PVP. This formulation achieved the desired response of 2.683% water content, 0.462 mg weight, and 0.369 mm thickness.